Dorland's illustrated medical dictionary (London : W.B. Saunders, 2000)
Comprehensive biomedical dictionary that reflects standard and current terminology derived from medicine and related disciplines. Changes involve deletions and additions in entries to conform with advances in knowledge, elaboration in certain fields, redrawn artwork, and rearrangement of certain entries. Official nomenclatures from various fields used in compilation. Also includes eponyms, acronyms, abbreviations, and botanical terms, as well as generic and trade names of many drugs. Entries include pronunciation, derivation, plural, definition, and subentries. Cross references. Illustrations throughout. 1st ed., 1900; 28th ed., 1994.
Previous ed.: 1994.
Keywords: Medicine -- Dictionaries; Medicine -- Dictionary -- English; Médecine -- Dictionnaires anglais